Preparation method of epoxy reversible resin-based three-dimensional braided hybrid structure composite material
By combining epoxy reversible resin with multi-axial three-dimensional braided hybrid structure prefabricated parts in thermosetting resin-based composite materials, the problem of irreversibility after curing is solved, the resin recycling and reuse is realized, and the thermal stability of the material is improved. Impact resistance reduces resource waste and environmental pollution.
Patent Information
- Application Number
- CN202211084971.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-06
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-09-06
AI Technical Summary
The existing thermosetting resin-based composite materials are irreversible after curing, resulting in uneven pouring and bubbles, which will cause waste of resources and environmental pollution, and will be difficult to apply to three-dimensional complex structures.
Epoxy reversible resin is used to combine with multi-axial three-dimensional braided hybrid structure prefabricated parts, cured by VARTM technology, and a stable covalent network is formed using acid anhydride and catalyst to achieve the recycling and reuse of the resin, increasing thermal stability and heat resistance.
It reduces the damage rate and waste amount of composite materials, reduces production costs, broadens application fields, improves the thermal stability and impact resistance of the materials, and reduces environmental pollution pressure.
Smart Images

Figure CN115302807B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fiber-reinforced composite materials, and in particular is a method for preparing an epoxy reversible resin-based three-dimensional braided hybrid structure composite material. Background Art
[0002] The composite material is a major trend in the development of contemporary materials science and engineering, and is also an important direction for the development of new materials technology. As a new type of material, composite materials can greatly improve the defects of single materials. Therefore, they have been widely used in various fields such as aerospace, national defense and military industry, land transportation, construction and civil engineering. Among modern composite materials, fiber-reinforced resin-based composite materials are more developed and widely used than other reinforced composite materials. They are increasingly valued by the domestic and foreign aerospace industry because of their high specific strength, high specific stiffness, good damping characteristics, long fatigue life, designability of mechanical properties, good molding process performance, and a wide variety of materials.
[0003] Thermosetting resin can be quickly molded using vacuum pumps and positive pressure pumps to achieve the purpose of mass production, and the products prepared with thermosetting resins have the characteristics of high quality, low price and low production cost in addition to high industrial application value. In the process of preparing composite materials, thermosetting resins are often used for curing. Once the thermosetting resin is cured, it will form an irreversible three-dimensional cross-linked network structure, which is insoluble and infusible. It cannot be remolded or dissolved like thermoplastic resins. If there are problems such as casting failure, bubbles, uneven resin penetration, and poor interface bonding, the entire composite material needs to be discarded. The three-dimensional weaving is difficult to manufacture and the cost is high, which will cause a lot of waste, extremely high production costs, and a large number of product discard problems. If these discarded composite materials are not recycled and processed in time, it will cause more serious environmental pollution and waste of resources. Summary of the invention
[0004] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing an epoxy reversible resin-based three-dimensional woven hybrid structure composite material.
[0005] The technical solution of the present invention to solve the technical problem is to provide a method for preparing an epoxy reversible resin-based three-dimensional woven hybrid structure composite material, characterized in that the method comprises the following steps:
[0006] Step 1, preparing normal yarn;
[0007] Step 2: Preparation of a multi-axial three-dimensional braided hybrid structure preform:
[0008] (2.1) Using carbon fiber as a 90° layer and moving it horizontally along the braiding machine by the distance of a yarn carrier;
[0009] (2.2) Kevlar fiber is used as the -θ° layer and UHMWPE fiber is used as the +θ° layer, and they are longitudinally moved along the row in the same direction on the braiding machine by the distance of a yarn carrier;
[0010] (2.3) The row where the 90° carbon fiber layer is located is further moved horizontally along the row by the distance of a yarn carrier, in the opposite direction to step (2.1);
[0011] (2.4) The columns where the -θ° Kevlar fiber layer and the +θ° UHMWPE fiber layer are located are further moved longitudinally along the columns in the same direction by the distance of a yarn carrier, in the opposite direction to step (2.2);
[0012] (2.5) adding a 0° carbon fiber layer between the 90° carbon fiber layer and the +θ° UHMWPE fiber layer;
[0013] (2.6) In the thickness direction, the normal yarn is passed through the gap between two adjacent rows of fibers from one side to any row on the other side to complete the exchange of the normal yarn;
[0014] (2.7) After beating, repeat steps (2.1) to (2.6) until the weaving of the multi-axial three-dimensional woven hybrid structure preform is completed;
[0015] Step 3, preparing epoxy reversible resin: mixing a multifunctional epoxy resin and anhydride compound, stirring at room temperature until the mixture is uniform; then adding zinc acetylacetonate, continuing to stir until the zinc acetylacetonate is dissolved to form a homogeneous system, and obtaining epoxy reversible resin after degassing;
[0016] Step 4, preparing composite materials: using VARTM technology, completely impregnating the multi-axial three-dimensional braided hybrid structure preform with epoxy reversible resin, and after curing, obtaining an epoxy reversible resin-based three-dimensional braided hybrid structure composite material.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The present invention uses epoxy reversible resin as a matrix and a multi-axial three-dimensional woven hybrid structure preform as a reinforcement to prepare a resin-based composite material. The preform is cured with epoxy reversible resin, and the preform and epoxy reversible resin are recycled. When bubbles, uneven pouring, and other problems occur during the curing process, the expensive preform is recycled, which greatly reduces the cost, reduces the damage rate of the composite material, and greatly reduces the generation of waste composite materials.
[0019] (2) The present invention uses anhydride and catalyst to replace the traditional curing agent to prepare an epoxy reversible resin with a stable covalent network, thereby improving the thermal stability of the epoxy reversible resin, and the glass transition temperature can reach up to 172°C, so that while ensuring mechanical strength, it has higher heat resistance than its thermosetting resin, can be used in high temperature environments, and broadens the application field of epoxy reversible resin. At the same time, because it also has the property of being recyclable, it alleviates economic pressure to a certain extent and avoids the problem of environmental pollution.
[0020] (3) The three-dimensional complex structure prefabricated parts have a tight internal structure, so curing must be done by VARTM liquid molding. Hot pressing curing or impregnation cannot ensure that the interior is full of resin, which restricts the application of epoxy reversible resin to three-dimensional complex structure prefabricated parts. The viscosity of the epoxy reversible resin of the present invention meets the curing viscosity requirement of VARTM (<1.7Pa.S), solves the problem that epoxy reversible resin can only be cured by hot pressing or impregnation principle, and realizes the preparation of composite materials by combining multi-axial three-dimensional woven hybrid structure prefabricated parts and epoxy reversible resin.
[0021] (4) The present invention uses PBO / PAN core-spun yarn obtained by electrospinning as Z yarn (i.e., normal yarn) to prepare a multi-axial three-dimensional woven hybrid structure preform, thereby increasing the friction resistance of the Z yarn during the weaving process. The -θ° layer uses Kevlar fiber, the +θ° layer uses UHMWPE fiber, the 0° layer and the 90° layer use carbon fiber, and the direction of the fiber in the 0° layer is perpendicular to the direction of the fiber in the 90° layer, and the Z yarn vertically runs through the entire fabric. Fibers with high strain and high toughness are configured on the back plate and the parts that are mainly subjected to impact damage, which helps to increase the composite material's ability to resist multiple impacts. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a three-dimensional simulation diagram of the overall structure of the multi-axial three-dimensional braided hybrid structure preform of the present invention;
[0023] Figure 2 It is a side simulation diagram of the overall structure of the multi-axial three-dimensional braided hybrid structure preform of the present invention;
[0024] Figure 3 This is an ultra-depth-of-field electron microscope image of the interlayer structure of the composite material of Example 1 of the present invention;
[0025] Figure 4 It is a curve diagram of impact load and displacement obtained after simply supported beam impact of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0026] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the claims of this application.
[0027] The present invention provides a method for preparing an epoxy reversible resin-based three-dimensional woven hybrid structure composite material (hereinafter referred to as the method), characterized in that the method comprises the following steps:
[0028] Step 1, preparing normal yarn: using PBO (poly(p-phenylene benzobisoxazole)) fiber as the core layer and PAN solution as the electrospinning solution, spinning PAN on the outside of the PBO fiber by using the electrospinning parallel electrode method, preparing a core-spun yarn with a core layer of PBO fiber and a skin layer of PAN fiber mesh, and using the core-spun yarn as the normal yarn for three-dimensional weaving;
[0029] Preferably, in step 1, the PAN solution is a DMF solution of PAN.
[0030] Preferably, in step 1, the specific process of the electrospinning parallel electrode method is: the specific process of the electrospinning parallel electrode method is: the PAN solution is transferred to two syringes respectively and the two syringes are fixed on their respective injection pumps respectively, and the needles of the two syringes are connected to two high-voltage power supplies with opposite polarities; the PBO fiber is used as the core yarn through the turntable and wound on the receiving roller; the injection pump injects at a flow rate of 0.5-0.6 mL / h, and a high voltage of ±6 kV is applied to the two needles to form an electric field. After the PAN solution is ejected from the needle, nanofibers are formed under the high-voltage electric field and gathered on the turntable. During the rotation of the turntable, the PAN nanofibers are coated on the surface of the PBO fiber, and after drying to remove the residual solvent, a core-spun yarn with a core layer of PBO fiber and a skin layer of PAN fiber mesh is obtained; the core yarn moving speed is 0.4 mm / s, the distance between the two needles is 12 cm, and the distance between the needle and the turntable is 10 cm.
[0031] Step 2, preparing a multi-axial three-dimensional braided hybrid structure preform (referred to as preform);
[0032] Preferably, the specific steps of step 2 are as follows:
[0033] (2.1) Using carbon fiber as a 90° layer and moving it horizontally along the braiding machine by the distance of a yarn carrier;
[0034] (2.2) Kevlar fiber is used as the -θ° layer and UHMWPE fiber is used as the +θ° layer, and they are moved longitudinally along the row in the same direction on the braiding machine by the distance of a yarn carrier;
[0035] (2.3) The row where the 90° carbon fiber layer is located is further moved horizontally along the row by the distance of a yarn carrier, in the opposite direction to step (2.1);
[0036] (2.4) The columns where the -θ° Kevlar fiber layer and the +θ° UHMWPE fiber layer are located are further moved longitudinally along the columns in the same direction by the distance of a yarn carrier, in the opposite direction to step (2.2);
[0037] (2.5) adding a 0° carbon fiber layer between the 90° carbon fiber layer and the +θ° UHMWPE fiber layer;
[0038] (2.6) In the thickness direction, the normal yarn is passed through the gap between two adjacent rows of fibers from one side to any row on the other side to complete the exchange of the normal yarn;
[0039] (2.7) After beating, repeat steps (2.1) to (2.6) until the weaving of the multi-axial three-dimensional woven hybrid structure preform is completed.
[0040] Preferably, in step 2, the angle θ can be changed according to specific needs, and can be other angles, such as 15°, 30° or 45°.
[0041] Step 3, preparing epoxy reversible resin: mixing a multifunctional epoxy resin and anhydride compound, stirring at room temperature for 5 to 10 minutes until the mixture is uniform; then adding zinc acetylacetonate, stirring for 20 to 30 minutes until the zinc acetylacetonate is completely dissolved to form a homogeneous system, and obtaining epoxy reversible resin after degassing;
[0042] Preferably, in step 3, the multifunctional epoxy resin is MY-0510, TT300 or E-51; the acid anhydride compound is methyltetrahydrophthalic anhydride or glutaric anhydride;
[0043] Preferably, in step 3, the mass ratio of the multifunctional epoxy resin, methyltetrahydrophthalic anhydride and zinc acetylacetonate is 0.9-1: 0.8-0.9: 0.02-0.04. The mass ratio of the multifunctional epoxy resin, glutaric anhydride and zinc acetylacetonate is 0.9-1: 0.2-0.3: 0.02-0.04.
[0044] Preferably, in step 3, the degassing process is: vacuum degassing in a vacuum drying oven at 60° C. to 80° C. for 15 to 25 minutes.
[0045] Step 4, preparing composite materials: using VARTM (vacuum assisted resin transfer molding) technology, completely impregnating the multi-axial three-dimensional braided hybrid structure preform with epoxy reversible resin, and after curing, obtaining an epoxy reversible resin-based three-dimensional braided hybrid structure composite material.
[0046] Preferably, in step 4, the VARTM process is specifically as follows: after placing the multi-axial three-dimensional woven hybrid structure preform into the mold, the mold is evacuated to make the interior of the mold a vacuum environment and exhaust the gas in the preform; then the epoxy reversible resin is injected from one end of the mold, and the pressure difference is used to drive the epoxy reversible resin to quickly pass through the surface of the preform, and at the same time penetrate in the thickness direction until the epoxy reversible resin completely wraps the multi-axial three-dimensional woven hybrid structure preform; when the epoxy reversible resin flows out from the other end of the mold, the resin completely fills the mold, and the resin injection is completed. At this time, the resin injection is stopped, and air is prevented from entering the mold; then the mold is placed in an oven, and after curing, an epoxy reversible resin-based three-dimensional woven hybrid structure composite material is obtained.
[0047] Preferably, in step 4, the curing process is: curing at 80-100° C. for 1-2 hours, then heating to 120-150° C. for curing for 1-4 hours, and then heating to 150-190° C. for curing for 3-8 hours.
[0048] Preferably, in step 4, the mold is preheated in an oven at 75° C. to 80° C. for 10 to 20 minutes to improve the flowability of the resin.
[0049] Alcoholic hydrolysis recovery of composite materials that still maintain a certain overall structure after service:
[0050] (1) Adding ethylene glycol in an amount of 55 to 60 times the mass of the composite material into a reaction kettle, heating the reaction kettle under vacuum at 180 to 190° C. for 22 to 24 hours, and then taking the reaction kettle out to complete the first alcoholysis reaction; after washing and drying, performing the second and third alcoholysis reactions according to the same process; and then ultrasonically cleaning the reaction kettle for 2 to 4 hours to obtain an alcoholysed preform and a resin mixed solution containing ethylene glycol;
[0051] (2) The prefabricated parts can be reused after drying;
[0052] The mixed resin solution containing ethylene glycol is subjected to a distillation process to obtain an epoxy reversible resin: since the boiling point of the epoxy reversible resin is relatively high, the entire distillation process is carried out under a vacuum state, and the ethylene glycol is distilled out by distillation to obtain the recovered epoxy reversible resin.
[0053] Example 1
[0054] (1) Preparation of normal yarn: Using PBO fiber as the core layer and PAN solution as the spinning solution, a core-covered yarn with PBO fiber as the core layer and PAN fiber mesh as the sheath layer was prepared by electrospinning parallel electrode method;
[0055] (2) preparing a multi-axial three-dimensional braided hybrid structure preform: using the core-spun yarn as the normal yarn, bundling the entire fabric in the thickness direction to obtain a multi-axial three-dimensional braided hybrid structure preform;
[0056] Among them, 0° and 90° yarns are made of T700 12k carbon fiber, -θ° is made of Kevlar fiber, and +θ° is made of UHMWPE fiber;
[0057] (3) Preparation of epoxy reversible resin: 316.2 g of epoxy resin TT300 and 283.8 g of methyltetrahydrophthalic anhydride were mixed and stirred at room temperature for 7 min until the mixture was uniform; then 9 g of zinc acetylacetonate was added and stirred for 20 min until the zinc acetylacetonate was completely dissolved to form a homogeneous system; and then vacuum degassing was carried out in a vacuum drying oven at 80° C. for 15 min to obtain epoxy reversible resin;
[0058] (4) Preparation of composite materials: The epoxy reversible resin was combined with a multi-axial three-dimensional woven hybrid structure preform by VARTM technology to cure the composite material, first at 100°C for 1 hour, then heated to 130°C for 2 hours, and then heated to 180°C for 3 hours to obtain an epoxy reversible resin-based three-dimensional woven hybrid structure composite material (referred to as the composite material). The fiber volume content of the composite material is 50%.
[0059] Performance test: According to the test standard, the composite material is cut into a size of 120mm×15mm×4mm for low-speed impact (i.e., simply supported beam impact) test, and the impact energy is selected as 2J.
[0060] Since the impact energy is small, the composite material is slightly damaged, which ensures the integrity of the prefabricated structure and has the value of recycling:
[0061] (1) Adding ethylene glycol in an amount 60 times the mass of the composite material into a reaction kettle, heating the reaction kettle under vacuum at 185° C. for 24 hours, and then taking the reaction kettle out to complete the first alcoholysis reaction; taking out the composite material, washing it, and drying it, and then performing the second and third alcoholysis reactions according to the same process; and then ultrasonically cleaning the reaction kettle for 2 to 4 hours to obtain a preform from which the resin has been completely removed and a resin mixed solution containing ethylene glycol;
[0062] (2) The prefabricated parts can be reused after drying;
[0063] The mixed resin solution containing ethylene glycol is distilled to obtain epoxy reversible resin: extraction starts when the temperature reaches 130°C, and the extraction efficiency reaches the maximum when the temperature rises to 165°C. The entire distillation process is carried out under vacuum, and ethylene glycol is distilled out by distillation to obtain pure epoxy reversible resin.
[0064] Comparative Example 1
[0065] (1) First, T700 12k carbon cloth is layered according to the setting of multi-axial weaving angles to obtain a laminated preform;
[0066] (2) Curing of composite materials: The epoxy reversible resin of Example 1 was combined with the laminated preform by VARTM technology to cure the composite material, first cured at 100° C. for 1 h, then heated to 130° C. for 2 h, and then heated to 180° C. for 3 h to obtain a laminated composite material as a control group. The fiber volume content of the laminated composite material was 50%.
[0067] Performance test: According to the test standard, the laminated composite material is cut into a size of 120mm×15mm×4mm for low-speed impact test, and the impact energy is selected as 2J.
[0068] Comparing the test results of Example 1 and Comparative Example 1, Figure 4 It can be seen that the peak value of the curve of the composite material of Example 1 is higher, and the maximum load it bears reaches 130N; while the maximum load of the laminated composite material of Comparative Example 1 is 110N. The slope of the curve of Example 1 is larger, indicating that the composite material of Example 1 can bear a larger load and better impact resistance than the laminated composite material of Comparative Example 1, and can also absorb more impact energy. This shows that the epoxy reversible resin-based three-dimensional woven hybrid structure composite material has better impact resistance.
[0069] Example 2
[0070] (1) Same as Example 1;
[0071] (2) Same as Example 1;
[0072] Performance test: According to the test standard, the composite material is cut into a size of 120mm×15mm×4mm and subjected to low-speed impact (i.e., simply supported beam impact), and the impact energy is selected as 2J.
[0073] (3) Preparation of epoxy reversible resin: 392.2 g of epoxy resin E-51 and 85.5 g of glutaric anhydride were mixed and stirred at room temperature for 20 min until the mixture was uniform; then 13.1 g of zinc acetylacetonate was added and stirred for 20 min until the zinc acetylacetonate was completely dissolved to form a homogeneous system; and then vacuum degassing was carried out in a vacuum drying oven at 80° C. for 15 min to obtain epoxy reversible resin;
[0074] (4) Preparation of composite materials: The epoxy reversible resin was combined with a multi-axial three-dimensional woven hybrid structure preform by VARTM technology to cure the composite material, first at 100°C for 2 hours, then heated to 130°C for 3 hours, and then heated to 160°C for 3 hours to obtain an epoxy reversible resin-based three-dimensional woven hybrid structure composite material. The fiber volume content of the composite material is 50%.
[0075] Performance test: According to the test standard, the composite material was cut into a size of 120mm×15mm×4mm and subjected to low-speed impact (i.e. simply supported beam impact), with an impact energy of 2J. After testing, the composite material can withstand an impact load of 135N.
[0076] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for preparing an epoxy reversible resin-based three-dimensional woven hybrid structure composite material, characterized in that: The method comprises the following steps: Step 1, preparing normal yarn; the normal yarn adopts core-spun yarn with a core layer of PBO fiber and a skin layer of PAN fiber mesh; Step 2: Preparation of a multi-axial three-dimensional braided hybrid structure preform: (2.1) Using carbon fiber as a 90° layer and moving it horizontally along the braiding machine by the distance of a yarn carrier; (2.2) Kevlar fiber is used as the -θ° layer and UHMWPE fiber is used as the +θ° layer, and they are longitudinally moved along the row in the same direction on the braiding machine by the distance of a yarn carrier; (2.3) The row where the 90° carbon fiber layer is located is further moved horizontally along the row by the distance of a yarn carrier, in the opposite direction to step (2.1); (2.4) The columns where the -θ° Kevlar fiber layer and the +θ° UHMWPE fiber layer are located are further moved longitudinally along the columns in the same direction by the distance of a yarn carrier, in the opposite direction to step (2.2); (2.5) adding a 0° carbon fiber layer between the 90° carbon fiber layer and the +θ° UHMWPE fiber layer; (2.6) In the thickness direction, the normal yarn is passed through the gap between two adjacent rows of fibers from one side to any row on the other side to complete the exchange of the normal yarn; (2.7) After beating, repeat steps (2.1) to (2.6) until the weaving of the multi-axial three-dimensional woven hybrid structure preform is completed; Step 3, preparing epoxy reversible resin: mixing a multifunctional epoxy resin and anhydride compound, stirring at room temperature until the mixture is uniform; then adding zinc acetylacetonate, continuing to stir until the zinc acetylacetonate is dissolved to form a homogeneous system, and obtaining epoxy reversible resin after degassing; The multifunctional epoxy resin is MY-0510, TT300 or E-51; the anhydride compound is methyltetrahydrophthalic anhydride or glutaric anhydride; The mass ratio of the multifunctional epoxy resin, methyltetrahydrophthalic anhydride and zinc acetylacetonate is 0.9-1: 0.8-0.9: 0.02-0.04; the mass ratio of the multifunctional epoxy resin, glutaric anhydride and zinc acetylacetonate is 0.9-1: 0.2-0.3: 0.02-0.04; Step 4, preparing composite materials: using VARTM technology, completely impregnating the multi-axial three-dimensional braided hybrid structure preform with epoxy reversible resin, and after curing, obtaining an epoxy reversible resin-based three-dimensional braided hybrid structure composite material.
2. The method for preparing the epoxy reversible resin-based three-dimensional woven hybrid structure composite material according to claim 1, characterized in that: In step 1, the preparation method of the core-spun yarn with a core layer of PBO fiber and a skin layer of PAN fiber mesh is as follows: using PBO fiber as the core layer and PAN solution as the electrospinning solution, and spinning PAN on the outside of the PBO fiber by using the electrospinning parallel electrode method.
3. The method for preparing the epoxy reversible resin-based three-dimensional woven hybrid structure composite material according to claim 2, characterized in that: In step 1, the specific process of the electrospinning parallel electrode method is: transfer the PAN solution to two syringes respectively and fix the two syringes on their respective injection pumps respectively, and the needles of the two syringes are connected to two high-voltage power supplies with opposite polarities; the PBO fiber is used as the core yarn through the turntable and wound on the receiving roller; the injection pump injects at a flow rate of 0.5-0.6 mL / h, and a high voltage of ±6 kV is applied to the two needles to form an electric field. After the PAN solution is ejected from the needle, it forms nanofibers under the high-voltage electric field and gathers on the turntable. During the rotation of the turntable, the PAN nanofibers are coated on the surface of the PBO fiber. After drying to remove the residual solvent, a core-wrapped yarn with a core layer of PBO fiber and a skin layer of PAN fiber mesh is obtained; the core yarn moving speed is 0.4 mm / s, the distance between the two needles is 12 cm, and the distance between the needle and the turntable is 10 cm.
4. The method for preparing the epoxy reversible resin-based three-dimensional woven hybrid structure composite material according to claim 1, characterized in that: In step 3, the stirring time of the multifunctional epoxy resin and the acid anhydride compound is 5 to 10 minutes; the stirring time after adding zinc acetylacetonate is 20 to 30 minutes.
5. The method for preparing the epoxy reversible resin-based three-dimensional woven hybrid structure composite material according to claim 1, characterized in that: In step 3, the degassing process is: vacuum degassing at 60°C to 80°C for 15 to 25 minutes.
6. The method for preparing the epoxy reversible resin-based three-dimensional woven hybrid structure composite material according to claim 1, characterized in that: In step 4, the VARTM process is specifically as follows: after placing the multi-axial three-dimensional woven hybrid structure preform into the mold, the mold is evacuated to make the inside of the mold a vacuum environment and exhaust the gas in the preform; then the epoxy reversible resin is injected from one end of the mold, and the pressure difference is used to drive the epoxy reversible resin to quickly pass through the surface of the preform, and at the same time penetrate in the thickness direction until the epoxy reversible resin completely wraps the multi-axial three-dimensional woven hybrid structure preform; after curing, an epoxy reversible resin-based three-dimensional woven hybrid structure composite material is obtained.
7. The method for preparing the epoxy reversible resin-based three-dimensional woven hybrid structure composite material according to claim 1 or 6, characterized in that: In step 4, the curing process is: curing at 80-100° C. for 1-2 hours, then heating to 120-150° C. for curing for 1-4 hours, and then heating to 150-190° C. for curing for 3-8 hours.
8. The method for preparing the epoxy reversible resin-based three-dimensional braided hybrid structure composite material according to claim 6, characterized in that: In step 4, the mold is preheated in an oven at 75°C to 80°C for 10 to 20 minutes to improve the flowability of the resin.
